"God Is Like a Drug…": Explaining Interaction Ritual Chains in American Megachurches1. Issue 3 (September 2014) - Wellman, James K.; Corcoran, Katie E.; Stockly‐Meyerdirk, Kate
<x xml:space="preserve">Abstract</x> Megachurches have been criticized as superficial sources of entertainment that do not produce significant feelings of belonging, moral responsibility, or spirituality. This article challenges popular criticisms of megachurches and, drawing on interaction ritual theory, proposes that megachurches are successful interaction ritual venues and powerful purveyors of emotional religious experience. We predict that these interaction rituals produce positive emotional energy, membership symbols that are charged with emotional significance, feelings of morality, and a heightened sense of spirituality. From a census of 1, 250 known megachurches in America, 12 were selected that closely represent the national megachurch profile. At each church, focus groups were conducted and attendees participated in a survey. We combine these data sources to provide a more comprehensive picture of the megachurch interaction ritual. The combined qualitative and quantitative results provide strong support for our predictions.